PENGEMBANGAN RUBRIK ANALITIK UNTUK ASESMEN KOMUNIKASI MATEMATIKA TERTULIS DALAM PEMECAHAN MASALAH MATEMATIKA - Arezqi Tunggal Asmana (Jurnal Pembelajaran Matematika, 2018)
Abstract: In mathematics learning, communication and problem solving are very important goals. To obtain information about that, a good assessment method is needed in the form of rubrics in each test. According to Danielson (1997), it is more appropriate to use analytical rubrics because the information obtained about students' strengths and weaknesses is clearer. This study aims to describe the development process and obtain a valid, practical and effective analytical rubric. This development relies on the Plomp (2010) model while compiling the Danielson (1997) rubric theory. The trial subjects were 2 mathematics teachers and 33 VIII grade students. From the validation and testing, an analytical rubric was obtained consisting of 6 aspects and 2 sub-aspects. Weight 1 for the first and fifth aspects and weight 2 for the other aspects. Sub aspects of the rubric are accuracy and completeness. Every aspect and sub aspect has 4 levels. The results of this study are valid, practical and effective analytical rubrics. Validity is shown by the average score of all validators is 3.1. Practicality is shown by (1) the correlation coefficient between classes is 0.980, 0.990, and 0.991 and (2) the average score of all teachers is 3.44. The effectiveness is shown by (1) the average percentage of total development scores is 7.7% and (2) 75.8% of students get positive KMT. Further research is needed for the description of the performance of the completeness of the aspects of the analytic rubric.Keywords: Pengembangan, Rubrik Analitik